Świat ptaków w staropolskich kolędach i pastorałkach (na materiale Kantyczek karmelitańskich z XVII i XVIII wieku) - Borejszo, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2011)
The article discusses the image of birds as documented in Kantyczki karmelitańskie [Carmelite canticles] from the 17th and the 18th centuries published by Barbara Krzyżaniak in 1980. Birds are to be found in more than 30 lyrics of Christmas carols (for the total number of 357 contained in the set under scrutiny). These include mainly domestic birds, very well-known both to the authors of the canticles and to the recipients and users of Polish Christmas carols and Christmas festivity songs. In total, about 60 species of birds are specified, including two exotic birds (the canary and the parrot). The bird’s realm was used in Christmas carols for different purposes, e.g. in the descriptions of the Bethlehem shed that is inhabited by petty birds, mentioned on account of the enumeration of gifts given to Jesus by shepherds, in accounts of the Flight to Egypt by the Holy Family, and in descriptions of the joy of the whole of the world of nature at the birth of the Saviour. It is worth noting that creators of Christmas carols did not limit themselves to just mentioning names of particular species of birds, but also provide a description of characteristics, sometimes a detailed one, such as the appearance and behaviour of its particular representatives. The carols include, for example, information on the habitat of birds, type and colouring of the plumage, common sounds made by various birds, staple food of birds, the shape of the beak and the size of the gullet. The birds pictured in the Christmas carols were either members of a village band up in the air (some sort of flying band), joyfully proclaiming Good News to the world (a motif often made used of in old-Polish Christmas carols and festive songs), or gathered at the manger to perform menial services and functions in real word reserved only for humans. Birds take on typically human behaviour, show human dispositions and fancies, customs and habits (e.g. wine or beer drinking in the nuptials).